Importance of the teaching – learning strategies to develop the reading and writing skills of English on the students in eighth, ninth and tenth years of basic education at Nueve de Octubre high school in Machala city, during the school year 2013-2014. - Cruz Bernabé, Luis Antonio; Romero Vásquez, María José (Machala : Universidad Técnica de Machala, 2015)
Nuestro trabajo de investigación se lleva a cabo en la ciudad de Machala, provincia de El Oro, en el "Nueve de Octubre" High School, para analizar la importancia de la enseñanza - estrategias de aprendizaje, para desarrollar las habilidades de lectura y escritura del idioma Inglés en los estudiantes de octavo, noveno y décimo año de educación básica durante el año escolar 2013-2014, con el fin de proporcionar las estrategias que ayudan a un mejor desarrollo y el aprendizaje de este idioma para el profesor y el estudiante. el marco teórico que hemos presentado en este trabajo se centra en los tipos de estrategias que existen y que podrían aplicarse para adquirir una mejor comprensión y aplicación de una segunda lengua, los factores involucran en el aprendizaje de la enseñanza y sus influencias y cómo se adaptan a lograr en las habilidades de lectura y escritos. el marco contextual se basa en el campo de la investigación realizada en la Unidad de Educación anterior, con el fin de observar la importancia que se le da a esta investigación dentro del campo de estudio y cómo ayudan en el proceso de enseñanza y aprendizaje en el desarrollo de las habilidades de lectura y escritura.
Our research work is performed in the city of Machala, Province El Oro, in the "NUEVE DE OCTUBRE” High School, to analyse the importance of teaching - learning strategies, to develop the reading and writing skills of the English Language in the students of Eighth, Ninth and Tenth Year of Basic Education during the school year 2013-2014, for the purpose of providing the strategies that help a better development and learning this language for the teacher and student. The theoretical framework we have presented in this work focuses on the types of strategies that exist and which could apply to acquire a better understanding and application of a second language, the factors involve in the teaching learning and their influences and how to adapt to achieve in the reading and writings skills. The contextual framework is based on field research conducted in the Education Unit above, in order to observe how important is given to this research within the field of study and how they help in the teaching and learning process in the development of reading and writing skills.
Keywords: TEACHING; READING; WRITING SKILL; STUDENT; LEARNING STRATEGY